In Situ Characterization and Modelling of Drying Dynamics for Scalable Printing of Hybrid Perovskite Photovoltaics - Ternes, Simon (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie, 2023)
Hybrid perovskite photovoltaics could play a vital role in future's renewable energy production. However, there are still severe challenges when scaling the technology. In this work, perovskite solution films drying in laminar and slot-jet air flows are investigated extensively by optical in situ characterization. The main results are a quantitative model of perovskite drying dynamics and a novel in situ imaging technique - yielding valuable predictions for large-scale perovskite fabrication.